Comparison of ABTS and DPPH assays in estimating the total antioxidant capacity of sweet potato (Ipomoea batatas) leaves - Villanueva, Joyce Efraim B.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study compared ABTS and DPPH assays in estimating the total antioxidant capacity of water extracts of sweet potato (Ipomoea batatas) leaves grown in the Philippines including two varieties (Inubi and Kinerots) with maturity of 1.5 months (young) and 3 months (mature). The total phenolic content (TPC) of the sweet potato leaves (SPL) determined using FolinCiocalteu method ranged from 72.422.64 112.989.45mg GAE100 g fresh leaves (FL). The validated ABTS and DPPH assays were determined to be linear (r20.95), with acceptable degrees of accuracy (80 120 recovery) and precision (RSD 10). The Total Antioxidant Capacity (TAC) values obtained using ABTS and DPPH assays were also higher than the limit of detection (LOD) value and limit of quantitation (LOQ) value indicating that the results were accurate and precise. TAC expressed in terms of Trolox Equivalent (TE) and Scavenging Activity (SA) of sweet potato leaves were estimated using the validated ABTS and DPPH assays. The estimated TAC of the SPL, using validated ABTS assay ranged from 88.730.76 93.140.83 mg TE100g FL while TAC using validated DPPH assay ranged from 158.264.13 205.523.80 mg TE100g FL. The SA of SPL using ABTS assay was reported to be 95.49 96.75 while SA of SPL using DPPH assay were 76.09 90.11. Differences in results were attributed to variations in varieties, methods, and the unique mechanisms involved in each assay. Method should be validated prior to official analysis to ensure its fitness for use for the specific sample matrix.
Thesis Classification: P (For Publication)
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Sweet potatoes -- Philippines -- Analysis